The relationship between information carrying words, memory and language skills in school age children with language impairment - Frizelle,Pauline; Harte,Jennifer; O'Sullivan,Kathleen; Fletcher,Paul; Gibbon,Fiona E. (PeerJ Preprints, 2016)
The receptive language measure information-carrying word (ICW) level is used extensively by speech and language therapists (SLTs) in the UK and Ireland. Despite this it has never been validated via its relationship to any other relevant measures. This study aims to validate the ICW measure by investigating the relationship between the receptive ICW score of children with language impairment (LI) and their performance on standardized memory and language assessments. Twenty-seven children with LI, aged between 5;07 and 8;11, completed a sentence comprehension task in which the instructions gradually increased in number of ICWs. The children also completed subtests from The Working Memory Test Battery for children and The Clinical Evaluation of Language Fundamentals – 4. Results showed that there was a significant positive relationship between both language and memory measures and children’s ICW score but that language was the greater contributor in children’s ability to do this task. ICW score is in fact a valid measure of the language ability of children with LI. However therapists should also be cognisant of its strong association with working memory when using this construct in assessment or intervention methods.
Keywords: memory; language impairment; Information-carrying words; assessment; children